Qualitative research : bridging the conceptual, theoretical, and methodological - Ravitch, Sharon M; Carl, Nicole Mittenfelner (2021)
"Designed with the graduate student in mind, Qualitative Research focuses on helping the reader cultivate and integrate theoretical, methodological and conceptual knowledge to provide insight into the interaction and to help understand the central concepts, topics and skills needed to engage in rigorous, valid, and respectful qualitative research. The authors have balanced communicating the foundations and processes of qualitative research with clarity and simplicity, while at the same time capturing its complexity and the multiple layers that were central to writing this book. Whether you are new to qualitative research or not, the goal for this book is to develop and deepen your understanding of an approach to research that seeks, designs for, and engages criticality in qualitative research. Every chapters begins with an overview and key objectives for the chapter. Many diverse examples illustrate key concepts throughout, along with a wide range of memos, conceptual framework narratives, graphics and much more. The new edition will include an earlier discussion of research ethics as crucial to students' inquiry, expanded information on individual methods for qualitative data collection, an expanded chapter on coding and other types of qualitative data analysis, and more thorough resource sections so students can further their qualitative research journey"--
Includes bibliographical references (pages 573-582) and index.
Keywords: Social sciences -- Research -- Methodology; Qualitative research -- Methodology